THE PROXIMITY SENSOR ROTATION OF A BICYCLE WHEEL - Стасюк, М. В.; Лебедев, Д. Ю. (Science-based technologies, 2013)
Becoming a full-fledged vehicle, a bicycle requires the use of instruments measuring the speed and distance traveled. Creating such a device requires the development of a method for measuring distance traveled and time spent. Time is measured by counting the oscillations of the quartz resonator, and the distance is measured by counting rotation of a wheel. Designed sensor enables more accurately and faster to determine the velocity of the bike. Hard-to-reach and expensive components are not used in the electrical circuit. Easy setup makes it simple to get a working scheme regardless of errors in component values and voltage bias in operational amplifiers. An electric current consumed by the sensor is less than a milliampere, and mostly depends on the current consumption of the amplifiers. No mechanical parts and ease of fixing of the sensor makes it easy to use and cheap to produce. Further improvement is possible by wireless communication with the computer.